Case study of business model adaptation in the travel industry: targeting generation z - Siagian, Erwin Iriyanto; Anisa, Nurul (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This research aims to analyze the adaptation of Travel Hajimena Berkah Jaya's business model in reaching Generation Z, a demographic group heavily influenced by digital technology. Using a descriptive qualitative approach, data was collected through in-depth interviews, direct observation, social media content analysis, and internal company documents. Thematic analysis techniques were used to identify key patterns in the company's business adaptation strategies. The results showed that the most effective strategy was marketing through collaboration with social media influencers, which significantly increased brand visibility and appeal to Generation Z, compared to other strategies such as mobile app development or data-driven service personalization. This strategy allows companies to reach a wide audience quickly and relevantly, according to this generation's preferences. This research provides practical insights for travel industry players to develop business adaptation strategies that are based on technology and market needs.